2009
DOI: 10.2169/internalmedicine.48.2072
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Retinal Phenotypes in an SCA7 Family

Abstract: We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition to this case report of HSP-like phenotype, and similarly to SCA1 and SCA3, spasticity is a clinical feature frequently observed in SCA7 patients [David et al, 1998;Durr, 2010;Giunti et al, 1999;Gu et al, 2000;Inaba et al, 2009;Johansson et al, 1998]. …”
Section: Spinocerebellar Ataxia Typementioning
confidence: 69%
“…In addition to this case report of HSP-like phenotype, and similarly to SCA1 and SCA3, spasticity is a clinical feature frequently observed in SCA7 patients [David et al, 1998;Durr, 2010;Giunti et al, 1999;Gu et al, 2000;Inaba et al, 2009;Johansson et al, 1998]. …”
Section: Spinocerebellar Ataxia Typementioning
confidence: 69%
“…29,32,33,34 Retinal degeneration may occur in the absence of pigmentary changes as well. 30 Macular and retinal dysfunction may be diagnosed prior to the appearance of funduscopic abnormalities via electroretinogram (ERG) 35 or ocular coherence tomography (OCT). 36 OCT shows thinning of the macula and retinal nerve fiber layer (RNFL).…”
Section: Ophthalmologic Features Of Sca7mentioning
confidence: 99%
“…8 There have been only six genetically confirmed and three suspected families of SCA7 in Japan thus far. The clinical features in half of those cases have been described in the literature [9][10][11][12][13] ; however, autopsy findings in Japanese SCA7 patients have not been reported. We performed a systematic clinical-neuropathological study in a Japanese autopsy case of genetically confirmed SCA7, providing evidence-based insights into the relationship between clinical symptoms and underlying pathomechanisms.…”
Section: Introductionmentioning
confidence: 99%